Dental caries in 12-year-old Brazilian adolescents: a comparative analysis of the last Three National Surveys - Viviane Elisângela GOMES; Mara VASCONCELOS; Milena Ribeiro GOMES; Andreia Maria Araújo DRUMMOND; Rosa Núbia Vieira de MOURA; Rafaela da Silveira PINTO; Renato Taqueo Placeres ISHIGAME; Joana Danielle Brandão CARNEIRO; Raquel Conceição FERREIRA (Brazilian Oral Research)
Abstract This study aimed to compare caries experience, prevalence of caries-free and untreated caries in 12-year-old adolescents, based on data from the national epidemiological surveys of 2003, 2010, and 2023, in Brazil and its regions, and to estimate the clinical consequences of untreated caries in 2023. A probabilistic cluster sample obtained from the three surveys was analyzed. The oral examinations for caries followed the recommendations of the World Health Organization. High caries experience was identified using the Significant Caries Index (SiC). Clinical consequences of untreated caries were measured using the PUFA index. A hypothesis test was conducted to verify differences in the means of DMFT and components, SiC, DMFT=0, and decayed teeth ≥ 1 among the surveys of 2003, 2010, and 2023. The analysis of data from 34,529 (2003), 7,328 (2010), and 6,704 (2023) adolescents revealed a significant reduction in DMFT from 2.47 (2003) and 2.07 (2010) to 1.67 (2023), and for the SiC group the reduction was from 6.30 (2010) to 5.90 (2023). A significant increase in the prevalence of caries-free was observed, from 34.64% (2003) and 43.49% (2010) to 49.88% (2023), and a significant reduction in the prevalence of adolescents with untreated caries from 48.47% (2003) to 36.85% (2023). Adolescents had on average 0.14 teeth with clinical consequences of untreated caries, with pulp involvement being the most frequent (80.02%), and 8.71% had PUFA≥1. Although 12-year-old adolescents showed a decrease in caries experience, the SiC group, untreated caries, and its clinical consequences represent sociodemographic inequities that need to be addressed.